Application of the Concept of Full-Cycle and Multi-Functional Cancer Rehabilitation - JIA Jie (康复学报)
With the increasing incidence of cancer and the prolonged survival of patients in China, a full-cycle and multi-functional cancer rehabilitation model has emerged as a new approach that aligns with disease progression and societal needs. This study focuses on the concept of comprehensive cancer rehabilitation and the promotion of multi-functional recovery throughout the entire cancer care journey. The comprehensive, multi-functional cancer rehabilitation model emphasizes the need for collaboration among clinical doctors, rehabilitation therapists, nurses, and social and family support systems. It also advocates for the active development of rehabilitation departments in oncology hospitals and the training of specialized personnel. Additionally, this study explores how to actively promote the widespread adoption and clinical application of the comprehensive, multi-functional cancer rehabilitation concept, addressing the diverse rehabilitation needs of cancer patients, including physical function, pain management, cognitive function, sleep quality, mental health, and aesthetic restoration. The goal is to enhance the overall quality of life for cancer patients and advance the field of cancer rehabilitation.